Combination of miRNA499 and miRNA133 Exerts a Synergic Effect on Cardiac Differentiation. (April 2015) - Pisano, Federica; Altomare, Claudia; Cervio, Elisabetta; Barile, Lucio; Rocchetti, Marcella; Ciuffreda, Maria Chiara; Malpasso, Giuseppe; Copes, Francesco; Mura, Manuela; Danieli, Patrizia; Viarengo, Gianluca; Zaza, Antonio; et al.
Abstract: Several studies have demonstrated that miRNA are involved in cardiac development, stem cell maintenance, and differentiation. In particular, it has been shown that miRNA133, miRNA1, and miRNA499 are involved in progenitor cell differentiation into cardiomyocytes. However, it is unknown whether different miRNA may act synergistically to improve cardiac differentiation. We used mouse P19 cells as a cardiogenic differentiation model. miRNA499, miRNA1, or miRNA133 were transiently over‐expressed in P19 cells individually or in different combinations. The over‐expression of miRNA499 alone increased the number of beating cells and the association of miRNA499 with miRNA133 exerted a synergistic effect, further increasing the number of beating cells. Real‐time polymerase chain reaction showed that the combination of miRNA499 + 133 enhanced the expression of cardiac genes compared with controls. Western blot and immunocytochemistry for connexin43 and cardiac troponin T confirmed these findings. Importantly, caffeine responsiveness, a clear functional parameter of cardiac differentiation, was increased by miRNA499 in association with miRNA133 and was directly correlated with the activation of the cardiac troponin I isoform promoter. Cyclic contractions were reversibly abolished by extracellular calcium depletion, nifedipine, ryanodine, and IP3R blockade. Finally, we demonstrated that the use of miRNA499 + 133 induced cardiac differentiation even in the absence of dimethyl sulfoxide. Our results show that the areas spontaneously contracting possess electrophysiological and pharmacological characteristics compatible with true cardiac excitation‐contraction coupling. The translational relevance of our findings was reinforced by the demonstration that the over‐expression of miRNA499 and miRNA133 was also able to induce the differentiation of human mesenchymal stromal cells toward the cardiac lineage. Stem Cells 2015;33:1187–1199